Analisis Isi Kekerasan Verbal dan Non Verbal dalam Film Kucumbu Tubuh Indahku - Dwi Adnyani, Ni Made Rosalia; Purnawan, Ni Luh Ramaswati; Pradipta, Ade Devia (E-Jurnal Medium; Vol 2 No 1 (2021): Jurnal Ilmu Komunikasi Vol 2 No 1 Tahun 2021, 2021)
ABSTRACT Memories of My Body film is one of the controversial films in Indonesia that is suspected to contain negative content for the younger generation, one of which is violence. The purpose off this research is to explain the verbal and non-verbal violence contained in Memories of My Body film used descriptive quantitative content analysis..The results showed thattthe Memories of My Body film featured verbal and non verbal violence 108 times. The most frequent violence is verbal violence 58 times with the most scenes appearing to be yelling as many as 30 times. Non-verbal violence that occurs in the film appears as many as 50 times with the most scenes that appear to be injured with objects or weapons as many as 20 times. In addition, in the Memories of My Body film, the violence looks the most dominant performed by men. Keywords: Content Analysis, Movies, Verbal Violence, Non Verbal Violence